Pets parents hate! : animal life cycles - Day, Trevor (Mankato, Minn. : Capstone Press, 2008)
Presents unusual pets and their care, including life cycle information.
Includes bibliographical references (p. 31) and index.
4.2
3-6
Keywords: Animal life cycles -- Juvenile literature; Pets -- Juvenile literature; Wild animals as pets -- Juvenile literature; Animal life cycles; Pets; Wild animals as pets; Life cycles (Biology); Pets; Wild animals as pets